Mutational pattern in the 5α reductase 2 (SRD5A2) gene in 46, XY Egyptian DSD patients. Issue 2 (July 2015) - Soliman, Hala; Amr, Khalda; El-Ruby, Mona; Mekkawy, Mona; Elaidy, Aya; Mazen, Inas
Abstract : Background: 5α-Reductase 2 deficiency (5αR2D) is an uncommon autosomal recessive disorder of sex development (DSD) characterized by the lack of masculinization in XY individuals because of failure of conversion of testosterone to dihydrotestosterone (DHT). Mutations in the steroid-5-α-reductase ( SRD5A2 ) gene, leading to functional gene impairment, are responsible for this disorder. More than 100 different mutations have been reported in autosomal recessive 5αR2D patients that could result in a 46, XY DSD. Most of these mutations are missense mutations; however, premature stop codons and both small and complete deletions of the SRD5A2 coding sequence were also detected. The aim of this study was to screen for mutations in the SRD5A2 gene in 46, XY DSD Egyptian patients with 5αR2D deficiency, and to characterize their clinical features. Patients and methods: Sixteen patients who were clinically diagnosed with 5αR2D were referred from Clinical Genetics and Endocrinology outpatient clinics. All patients were subjected to full clinical examination, with particular emphasis on external genitalia, cytogenetic studies using the G-banding technique, and hormonal assays of both basal and post-HCG levels, levels of serum testosterone and its precursors, and dihydrotestosterone levels; imaging was performed, including pelvic sonography, and molecular studies were conducted by sequence analysis. Results: Clinical results revealed positive parental consanguinity in 87.5% of the cases. Sex of rearing was male in eight patients and female in the other eight patients. Microphallus, ambiguous or female genitalia, was a frequent phenotype in all patients. Hormonal results showed an elevated testosterone/dihydrotestosterone ratio in eight patients. Molecular analysis of all five exons of the SRD5A2 gene in all patients revealed the presence of five different SRD5A2 missense point mutations (G34R, Y91H, Q56R, G196S, and A207D): 7/16 patients were found to be homozygous for the most commonly reported G34R Egyptian mutation; 2/16 and 4/16 patients were homozygous for the Y91H and G196S mutations, respectively; one proband was homozygous for the Q56R mutation; the last two patients were heterozygous for the G34R and A207D mutations, respectively: the first one of them was homozygous, whereas the second was heterozygous for the V89L polymorphism. Conclusion: This study reported and added four mutations to the previously reported mutational pattern of the SRD5A2 gene in Egyptian patients.